ANALYSIS OF APPLICATION OPPORTUNITIES OF CLUSTER APPROACH INTHE FIELD OF COCOONİNG AND SERICULTURE IN AZERBAIJAN (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2026)
The application of a cluster approach in the field of cocoon production and sericulture offers many advantages, based on the principle that various entities operating in this sector come together to share resources and knowledge. Accordingly, this research has analyzed the current state of sericulture and silk production in the country, the concept of clustering, and the benefits of the cluster approach. Furthermore, by studying the experiences of leading countries in sericulture, such as China, India, and Uzbekistan, the study has developed proposals for applying the cluster approach in this field in the country.